Assessing Organizational Readiness for Change of UTama’s Lecturers - et. al., Sunardi Sembiring Brahmana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The escalating uncertainty as a result of the rapidly changing business environment, forces organizations to make changes in order to adapt to its environment. The ability to make change depends on the readiness for change of each member of the organization. The readiness for change of organizational members is therefore important to measure. This research is intended to measure and describe the readiness for change of UTama lecturers. To measure this readiness for change, a total of 160 questionnaires is distributed to UTama lecturers. A total 106 of them were returned and could be analyzed further. Descriptive statistics show that UTama lecturers’ readiness for change is marginally low. This means that the lecturers’ resistance to be involved in the change process is relatively high.